Patterns of work Exploring ways of working in logistics management - Medina, Benedicto Benjamin V. (Ann Arbor Michigan Bell & Howell Information and Learning Company, 2000)
The Complex shift of the economy from the industrial age to a knowledge-driven future has placed new demands on the logistics professional to manage work and relationships, improve on existing capabilities, and develop new skills. Conventional approaches of using technology to increase efficiency and decrease cost may not be sufficient to address the new challenges. One promising management approach is to focus on enhancing people's ways of working. Central to this approach is the development of patterns--the explicit representations or expressions of the essential elements of ways of working. The concept of patterns originated from architecture and urban planning and recently emerged as a subject of study in management research. In this dissertation, we explored the applicability and usefulness of using the pattern concept to guide logistics activities. We implemented the pattern concept in three case studies. First, we used patterns to document and refine previously implicit or semi-explicit ways of work that had evolved within a line organization as part of a strategic initiative. Second, we applied the pattern concept in a deliberate process of supporting business strategy implementation. Third, we integrated pattern development to a training process and showed how patterns could be used to elicit, document, and communicate key concepts and Ideas. In addition to the case studies, we also examined the fundamental issues in knowledge management and developed a pattern-based conceptual framework. To contribute to the body of knowledge on patterns, we also summarized the insights gained and lessons learned from the case study experience. Although we could not unequivocally conclude that patterns enhanced people's ways of working, the results of the research suggest the usefulness of patterns in supporting various aspects of logistics activities.--Abstract.
Thesis (Ph.D.)--Northwestern University, 1999.
Keywords: Production management; Logistics